Forehead plaque: a presenting skin sign in tuberous sclerosis. Issue 3 (March 1987) - Fryer, A E; Osborne, J P; Schutt, W
Abstract : The forehead plaque can be the earliest skin manifestation of tuberous sclerosis and its presence may lead to early diagnosis and appropriate genetic counselling.